Optimalisasi Artificial Intelligence untuk Promosi Produk Ekonomi Kreatif melalui Media Sosial - Ahmad Mansur; Septa Intiar; Umar Abdul Jabbar (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the use of Artificial Intelligence (AI) in promoting creative economy products in Central Java's tourist areas, particularly through social media. In today's digital era, developments in information and communication technology, including artificial intelligence, have opened up new opportunities for more efficient, personalized, and data-driven marketing strategies. Creative economy products such as batik, handicrafts, and local culinary delights can gain broader exposure through innovative digital promotional approaches. However, Micro, Small, and Medium Enterprises (MSMEs) in Central Java's tourist areas, such as Jatirejo Village in Semarang, known for its palm fruit (kolang-kaling), still face various challenges in adopting this technology. This study used a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with MSMEs, field observations, and documentation related to their digital promotional activities. The results indicate that limited human resources, lack of digital literacy, minimal understanding of the concept and application of AI, and inadequate technological infrastructure are the main obstacles in implementing AI for promoting creative economy products. However, this study also identified significant opportunities for optimizing AI implementation. These opportunities include training and mentoring for MSMEs, collaboration between the government, academia, and the private sector, and the development of equitable digital infrastructure. This study provides strategic recommendations to enhance MSME competitiveness in the digital era and strengthen synergies between technology and the creative economy. These findings are expected to serve as an important reference for policymakers and businesses in formulating adaptive and sustainable AI-based promotional strategies.